Pigs make me sneeze! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2009)
Gerald, a cautious and pessimistic elephant, believes he is allergic to his best friend, the optimistic and occasionally reckless Piggie, and is concerned that he will need to stay away from his pal forever.
0.7
K-3.
K-3
Keywords: Allergy -- Juvenile fiction; Elephants -- Juvenile fiction; Swine -- Juvenile fiction; Allergy -- Fiction; Elephants -- Fiction; Pigs -- Fiction; Allergy -- Fiction; Elephants -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)